Online test using displacement force mixed control. - Pan, Peng
This paper proposes an online test technique that employs mixed control of displacement and force. Two types of mixed control, 'displacement force combined control' and 'displacement force switching control' are proposed. In displacement force combined control, one jack is operated by displacement control and another is operated by force control. Validity of the combined control technique is demonstrated by a series of online tests applied to a base isolated structure subjected to horizontal and vertical ground motions simultaneously. The substructuring technique is employed in the tests and the base isolation layer is tested, with the rest of the structure modeled in the computer. Displacement control and force control were adopted for simulating the horizontal and vertical response, respectively. Both displacement and force control were implemented successfully despite interference between the two jacks. Earthquake responses of the base isolated structure involving the effects of varying axial forces on the horizontal hysteretic behavior of the base isolation layer were simulated. In the displacement force switching control, the jack was operated by displacement control when the test specimen was flexible but switched to force control once the specimen became stiff. Validity of the switching control technique was also checked by a series of online tests applied to the base isolated structure subjected to vertical ground motions. Switching between displacement control and force control was achieved when the axial force applied to the base isolation layer changed from tension to compression or from compression to tension. Both the displacement and force control were successful even with many rounds of switching. The test revealed that large accelerations occured on the floor immediately above the base isolation layer at the instants when the axial force of the base isolation layer changed from tension to compression.
Keywords: Online test; Mixed control; Combined control; Switching control; Substructure; Base isolation